Effect of nutritional factors and growth conditions on biosurfactant production by Pseudomonas mendocina and Pseudomonas oleovorans isolated from oil contaminated soil in Jeddah city - Motwali, Ebtihal A.; Aly, Magda M.; Qari, Huda A.; Alhazmi, Nuha M. (Journal of Contemporary Medical Sciences, 2021)
Objectives: The current study aimed to investigate the impact of different nutritional factors and growth conditions on biosurfactant production by bacterial isolates (EMB16 and EMB21) isolated from oil-contaminated soil samples. Methods: Based on the used quantitative and qualitative screening method in current study, the selected bacterial isolates showed a high potential to produce biosurfactant. Results: By using 16S rRNA sequence analysis, the bacterial isolates EMB16 and EMB21 were found to be closely related to Pseudomonas mendocina and Pseudomonas oleovorans, respectively. The ultimate yields of biosurfactant (8.06±0.06 mg/ml) by Ps. mendocina EMB16 was with corn oil as a carbon source, urea as a nitrogen source, C/N ratio of 30, pH value of 7, and 2% inoculum size. For Ps. oleovorans EMB21, the maximum biosurfactant production (4.68±0.14mg/ml) was achieved by diesel oil as a carbon source, urea as a nitrogen source, C/N ratio of 30, pH of 7, and 5% size of inoculum. The best incubation period and temperature for the examined strains was 168 hrs. at 37℃. Conclusion: The results proved that Ps. mendocina EMB16 was the most efficient biosurfactant producer as it showed the greatest amount of biosurfactant concentration and lowestvalue of surface tension measurement with an emulsification index of 67±6%.